Designing Risk Management Ramework on Fundamental, Technical Variables of Normal Period and Crisis With Stock Return - Nurchairul Akbar Saad (Journal of Social Science, 2023)
In the past two years, the global and Indonesian economies have been severely impacted by the COVID-19 pandemic, leading to below-target and negative growth rates worldwide. Indonesia declared the pandemic in March 2020, resulting in disruptions and lower-than-expected economic growth, with the first quarter of 2020 recording 2.97% growth compared to a consensus of 3.5-4.0%. Key sectors like manufacturing, retail, construction, and mining contracted, while household consumption dropped to 2.84% from 5.01% the previous year. This summary presents inflation and economic growth data in Indonesia as of October 2020 from the Central Statistics Agency. The research outcomes serve as reference material for government policy-making during crises, offer insights to infrastructure issuers in the capital market, assist investors in stock transactions and projections, and provide general knowledge about Indonesia's capital market.